KONJUNGSI BAAI DALAM KALIMAT BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (KIRYOKU, 2018)
(Title: Conjunction Baai in Japanese Sentence) This research examines the structure and the meaning of baai. The method used in this research is the method of agih and descriptive. Baai is a keishiki meishithat functions as a conjunction. Baai combines clauses with clauses in compound sentences. The subordinate clause baai expresses the ingakankei relation with meaning toki, joutai, and jijou. Baai can be attached to nouns, verbs, adjectives.Keywords: baai; keishikimeishi; conjunction